Selective photocatalytic reduction of CO2 to methanol in CuO-loaded NaTaO3 nanocubes in isopropanol - Xiang, Tianyu; Xin, Feng; Chen, Jingshuai; Wang, Yuwen; Yin, Xiaohong; Shao, Xiao (Beilstein Journal of Nanotechnology, 2016)
A series of NaTaO3 photocatalysts were prepared with Ta2O5 and NaOH via a hydrothermal method. CuO was loaded onto the surface of NaTaO3 as a cocatalyst by successive impregnation and calcination. The obtained photocatalysts were characterized by XRD, SEM, UV–vis, EDS and XPS and used to photocatalytically reduce CO2 in isopropanol. This worked to both absorb CO2 and as a sacrificial reagent to harvest CO2 and donate electrons. Methanol and acetone were generated as the reduction product of CO2 and the oxidation product of isopropanol, respectively. NaTaO3 nanocubes loaded with 2 wt % CuO and synthesized in 2 mol/L NaOH solution showed the best activity. The methanol and acetone yields were 137.48 μmol/(g·h) and 335.93 μmol/(g·h), respectively, after 6 h of irradiation. Such high activity could be attributed to the good crystallinity, morphology and proper amount of CuO loading, which functioned as reductive sites for selective formation of methanol. The reaction mechanism was also proposed and explained by band theory.
Keywords: CO2 reduction; CuO loading; isopropanol; NaTaO3 nanocubes; photocatalysis